Microarrays application in life sciences: The beginning of the revolution - de Travensolo, Regiane Fátima (2021)
Previous to Next Generation Sequencing (NGS), a different technology allowed science to drive through the roads of genetic analysis, the microarray technology. Shortly, microarrays consist of a grid of spots, with each spot containing single-stranded DNA sequences attached to a solid surface. For microarray analysis, the mRNA must be extracted from the sample and converted to a labeled cDNA strand, and later added to the microarray device. The DNA sequences on the microchip are fragments of genes of interest, and once the sample is added to the microarray, the cDNA strands from the sample hybridize with the strands fixed on the device if they are matching. In that way, a single device allows the analyst to check for the presence of several genes at once. In this chapter, the reader will learn precisely how microarray analysis works, concepts to produce in-lab microarrays, and the main research areas applying the microarray technology.